PENGARUH STRATEGI PEMBELAJARAN INKUIRI DAN EKSPOSITORI TERHADAP HASIL BELAJAR IPA SISWA KELAS 5 SEKOLAH DASAR - Prayekti, Prayekti (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Aims the study to determine the effect of expository inquiry learning and the learning outcomes science of students of class V elementary school physics. Students who are going through puberty have a curiosity so high that teachers provide learning facilities with inquiry learning strategy, which is compared with expository learning strategy. This research was conducted in class V elementary School, one class is learning physics by inquiry learning strategy as experimental class and other classes with expository as the control class. The study was conducted in East Jakarta elementary School, pretest value, the value of learning, and the value of post-test were analyzed by ANCOVA. The results showed that administration of inquiry learning system can significantly increase the value of physics students better or higher than expository learning system with R Square .701. Keywords: inquiry, expository, IPA, pretest, posttest, learning strategies.